2017
DOI: 10.1080/09638237.2017.1294738
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the nature and intensity of stress following employment among people with severe mental illness receiving individual placement and support services: an exploratory qualitative study

Abstract: Competitive work changed the nature of stress and was mostly associated with a decrease in stress level. Adjunctive interventions aiming to buffer self-stigma or help participants use more adaptive coping mechanisms may merit investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…This may help explain why job tenure in IPS programmes is often low, averaging 12.8 weeks for all study participants, and 20.0 weeks for those who worked, as reported in a synthesis of eight trials with study durations of a year or more . One factor influencing the experience of stress perceived by working IPS clients in our study was if they could socialise with co-workers, and the support they consequently received (Besse et al, 2017): these results reflect the importance of a friendly work environment, confirming Rüsch's conclusion of stigma-related stress in this population (Rüsch et al, 2014).…”
Section: Categories Topics Quotessupporting
confidence: 81%
See 1 more Smart Citation
“…This may help explain why job tenure in IPS programmes is often low, averaging 12.8 weeks for all study participants, and 20.0 weeks for those who worked, as reported in a synthesis of eight trials with study durations of a year or more . One factor influencing the experience of stress perceived by working IPS clients in our study was if they could socialise with co-workers, and the support they consequently received (Besse et al, 2017): these results reflect the importance of a friendly work environment, confirming Rüsch's conclusion of stigma-related stress in this population (Rüsch et al, 2014).…”
Section: Categories Topics Quotessupporting
confidence: 81%
“…In a companion paper (Besse, Poremski, Laliberté, & Latimer, 2017), drawing on the same set of interviews, we focused on the transition from unemployment to employment. We concluded that, in general, entry into competitive work was mostly associated with a decrease in stress level (consistent with the observation from IPS trials, noted in the introduction, that, if anything, being assigned to IPS leads to fewer hospitalisations).…”
Section: Categories Topics Quotesmentioning
confidence: 99%
“…Studies targeting solely clients of IPS accounted for most of the articles retrieved ( n = 15, 57.7%) (Alverson et al, 1995; Areberg et al, 2013; Becker et al, 2007, Besse et al, 2017, 2018; Boycott et al, 2015; Coombes et al, 2016; Gammelgaard et al, 2017; Huff et al, 2008; Johnson et al, 2009; Koletsi et al, 2009; Lexen et al, 2013a, 2013b; Liu et al, 2007; Nygren et al, 2016). An additional four articles focused on clients among other stakeholders (15.4%).…”
Section: Resultsmentioning
confidence: 99%
“…We documented the qualitative methodologies applied in the retrieved studies based on the authors’ verbatim descriptions of the methodological approaches they used; in other words, we did not apply our own methodological labels to what was described in the studies, but rather relied on the face value of the authors labels. Eight studies stated they used a grounded theory approach ( n = 8, 30.8%; Becker et al, 2007; Besse et al, 2017, 2018; Coombes et al, 2016; Glover & Frounfelker, 2011, 2013; Lexen et al, 2016; Liu et al, 2007). Seven studies stated they used content analysis ( n = 7, 26.9%; Areberg et al, 2013; Glover & Frounfelker, 2013; Hasson et al, 2011; Kostick et al, 2010; Nunes et al, 2011; Nygren et al, 2016; Salyers et al, 2008; Whitley et al, 2010), which included purely inductive content analysis, deductive content analysis, and directed content analysis approach.…”
Section: Resultsmentioning
confidence: 99%
“…Individual placement and support (IPS) programs are effective in aiding Singaporeans with psychiatric illnesses in obtaining and keeping competitive jobs [105]. IPS reduced stress after they found work and interactions with co-workers dispelled negative self-thoughts and self-stigma [105]. As part of the NMHB, a Job Club was established and run collaboratively by occupational therapists, medical social workers and job placement officers [101].…”
Section: Stigma Related To Psychiatric Illnesses and Advancement Of Amentioning
confidence: 99%